Lexico-phraseological means of expressing the emotional evaluation function of head-lines (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article gives the language peculiarities studing of newspapers, shows the increasing of emotional evaluation of head-lines due to the usage of big quantity of lexico-phraseological means pleated in a language system of   kindred languages. The paper analyzes their usage reasoned with stylistic tasks and author’s intention.
Keywords: colloquial vocabulary; slangy vocabulary; lexical compatibility of words; phraseological units